Corporate environmentalism and public policy - Lyon, Thomas P.; Maxwell, John W. (Cambridge Cambridge University Press, 2004)
This is the first book to provide a hard-headed economic view of the voluntary approaches to environmental issues, especially toxic chemicals, waste disposal and global warming, that have become prominent in recent years. Corporate environmental initiatives are seen as a tool for influencing the behaviour of environmental activists, legislators, and regulators, though they may have ancillary benefits such as attracting 'green' consumers or reducing costs. Equally, government voluntary programs are seen as a way to achieve modest environmental results when political resistance to mandatory policies is high. Rigorous analysis is illustrated with numerous case studies drawn from the US, Europe, and Japan, while technical details are relegated to appendices, and each chapter highlights implications for corporate strategy and public policy. Although rooted in economic theory, this book will appeal to business strategists and policy practitioners, as well as scholars and researchers.
Keywords: Business enterprises -- Environmental aspects; Corporations -- Environmental aspects; Public - Private sector cooperation; Environmental policy; Industrial management -- Environmental aspects; Industries -- Self-regulation